Costal and Auricular Cartilage Grafts for Nasal Reconstruction: An Anatomic Analysis. (October 2017) - Ho, Thuy-Van Tina; Cochran, Thomas; Sykes, Kevin J.; Humphrey, Clinton D.; Kriet, J. David
Objectives: The aim of this study was to measure the length, width, and surface area of costal and auricular cartilage harvested for grafting in rhinoplasty and nasal reconstruction. We also compared the sizes of ear cartilage grafts harvested from the anterior and posterior approaches. Methods: Fifty-eight nasal reconstructive surgeries requiring rib or ear cartilage were performed by 2 facial plastic surgeons from February 2015 through January 2016. Among the 57 cases that met inclusion criteria, they comprised of 33 costal cartilage grafts and 24 auricular cartilage grafts (17 via anterior approach and 7 via posterior approach). Results: The mean length, width, and surface area for the auricular cartilage grafts were 3.39 cm, 1.22 cm, and 4.38 cm 2, respectively. The mean length, width, and surface area of the costal cartilage grafts were 4.21 cm, 1.46 cm, and 17.87 cm 2, respectively. The differences in length, width, and surface area between the anterior versus posterior approach groups were all statistically significant. Conclusions: In our study, ear cartilage grafts harvested from the posterior approach had significantly greater length, width, and surface area. While this analysis has several limitations, it sets quantitative norms for costal and auricular cartilage harvest that can aid in surgical planning.